Mathematical analysis of work aorto-mesenteric "forceps" - A. G. Tonyan; R. Sh. Muslimov; O. I. Zhdamarova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
It is generally accepted that the diagnostic criteria for hemodynamically significant compression of the left renal vein are the anteroposterior size of the renal vein determined by ultrasound examination in the narrowed area of 1.5–2.5 mm or less. Purpose of the study: determine the features of the work of the aorto-mesenteric "forceps" on the basis of mathematical analysis. A polypositional ultrasound examination of the kidneys, renal arteries and veins was carried out in 6 positions (standing, sitting, on the back, on the stomach, on the right and left sides). The parameters of the aorto-mesenteric "forceps" (AMP) were determined on the basis of ultrasound and mathematical analysis. Research results: In different positions of the body, the velocity indicators of arterial and venous blood flow, the diameter of the renal (PV) vein in the main part, at the gate and in the AMP change. Pressure fluctuations in the left renal vein are position-dependent and are a factor influencing the work of the aorto-mesenteric forceps.